Perspectives and experiences in the development of a software architecture course (2008)
The rapid evolution of technology and IT for business support, as well as the new demands on engineering curricula for the development of skills rather than just the presentation of thematic contents, imposes a series of challenges for the design and definition of a software architecture course. Proposals for the development of skills necessary for software engineering practice, regarding architecture, focused on technology, are not flexible enough on the long term, and are not proper for the development of criteria necessary for students to apply architecture in real world projects. Conversely, solutions based solely on conceptual contents do not give enough room for students to develop design skills in the area of software architecture, and particularly, the impact that technology has on architecture and over all system quality. In this paper, we present the evolution of our design for a software architecture course for undergraduate students. Particularly we introduce a proposal for a new perspective for the design of this courseÍ¾ this perspective is based on three broad areas: business, design and technologies using active learning methodologies.